Nature's carriers: leveraging extracellular vesicles for targeted drug delivery - Qi Chen; Yuyi Zheng; Xuhong Jiang; Yi Wang; Zhong Chen; Di Wu (Taylor & Francis Group, 2024)
With the rapid development of drug delivery systems, extracellular vesicles (EVs) have emerged as promising stars for improving targeting abilities and realizing effective delivery. Numerous studies have shown when compared to conventional strategies in targeted drug delivery (TDD), EVs-based strategies have several distinguished advantages besides targeting, such as participating in cell-to-cell communications and immune response, showing high biocompatibility and stability, penetrating through biological barriers, etc. In this review, we mainly focus on the mass production of EVs including the challenges and strategies for scaling up EVs production in a cost-effective and reproducible manner, the loading and active targeting methods, and examples of EVs as vehicles for TDD in consideration of potential safety and regulatory issues associated. We also conclude and discuss the rigor and reproducibility of EVs production, the current research status of the application of EVs-based strategies to targeted drug delivery, clinical conversion prospects, and existing chances and challenges.